2018
DOI: 10.17576/jsm-2018-4706-22
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Stored Core Oil Palm Trunk (COPT) Sap Identifying Proteins Related to Stress, Disease Resistance and Differential Gene/Protein Expression

Abstract: Oil palm is the major crop grown and cultivated in various Asian 14.283, 25.543, 29.757, 30.549, 31.511, 34.585 and 84.395 kDa, respectively 14.283, 25.543, 29.757, 30.549, 31.511, 34.585

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was reported that the presence of lithium, which is a GSK-3 inhibitor, at 3g L −1 LiCl and 2 g L −1 LiCl on PDA inhibited the mycelia growth of C. cinerea and fruiting body development of P. djamor [45]. Receptor-like serine/threonine protein kinase was ob served in the core of OPT [46], which could have possibly disrupted the cell differentiation process of mycelia, and eventually inactivated fruiting body development in T3 and T6. Tables 5 and 6 show the growth and yield for treatments that successfully produced fruiting bodies.…”
Section: Growth and Yield Of Mushroommentioning
confidence: 99%
“…It was reported that the presence of lithium, which is a GSK-3 inhibitor, at 3g L −1 LiCl and 2 g L −1 LiCl on PDA inhibited the mycelia growth of C. cinerea and fruiting body development of P. djamor [45]. Receptor-like serine/threonine protein kinase was ob served in the core of OPT [46], which could have possibly disrupted the cell differentiation process of mycelia, and eventually inactivated fruiting body development in T3 and T6. Tables 5 and 6 show the growth and yield for treatments that successfully produced fruiting bodies.…”
Section: Growth and Yield Of Mushroommentioning
confidence: 99%
“…Data processing was conducted according to previous studies 12,13 . Raw files for each biological replicate were analysed together using the MaxQuant software (version 1.5.3.30) 14 .…”
Section: Protein Identification and Quantificationmentioning
confidence: 99%